2019
DOI: 10.1104/pp.19.00100
|View full text |Cite
|
Sign up to set email alerts
|

BES/BZR Transcription Factor TaBZR2 Positively Regulates Drought Responses by Activation of TaGST1

Abstract: BRI1-EMS suppressor (BES)/brassinazole-resistant (BZR) family transcription factors are involved in a variety of physiological processes, but the biological functions of some BES/BZR transcription factors remain unknown; moreover, it is not clear if any of these proteins function in the regulation of plant stress responses. Here, wheat (Triticum aestivum) brassinazole-resistant 2 (TaBZR2)-overexpressing plants exhibited drought tolerant phenotypes, whereas downregulation of TaBZR2 in wheat by RNA interference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 76 publications
2
116
0
Order By: Relevance
“…TaBZR2, a BES1 and BZR1 homolog in wheat (Triticum aestivum), promotes drought responses by inducing the expression of wheat glutathione S-transferase1, which is involved in superoxide scavenging (Cui et al, 2019). Likewise, studies in tomato (Solanum lycopersicum) revealed that BRs promote drought tolerance, whereas overexpression of the BR receptor gene SlBRI1 had an opposite effect (Nie et al, 2019).…”
Section: Tissue-specific Modulation Of the Br Pathway Allows For Incrmentioning
confidence: 99%
“…TaBZR2, a BES1 and BZR1 homolog in wheat (Triticum aestivum), promotes drought responses by inducing the expression of wheat glutathione S-transferase1, which is involved in superoxide scavenging (Cui et al, 2019). Likewise, studies in tomato (Solanum lycopersicum) revealed that BRs promote drought tolerance, whereas overexpression of the BR receptor gene SlBRI1 had an opposite effect (Nie et al, 2019).…”
Section: Tissue-specific Modulation Of the Br Pathway Allows For Incrmentioning
confidence: 99%
“…Reports that overexpression of GmNFYA3 [31], Cdt-NFYC1 [11], RING-H2 [41] and GmTGA17 [42] conferred increased ABA sensitivity and drought tolerance in transgenic lines, were confirmed in this study ( Figure 3). Moreover, some physiological indices, especially the SWP, were not reported in previous reports [6,27,32,37]. One to six CCAAT cis-acting elements were detected in the promoters of all the marker genes used in this study (Table S2).…”
Section: Discussionmentioning
confidence: 49%
“…Drought is more widespread and damaging than salt stress [3]. Adaptation to drought involves complex regulatory networks involving control of water flux and cellular osmotic adjustment [4][5][6]. ABA regulates drought tolerance in plants by regulating stomatal aperture and modulating drought-responsive genes such as AP2/ERF and MYB family members that play important roles under drought stress [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Reports that overexpression of GmNFYA3 [31], Cdt-NFYC1 [11], RING-H2 [41] and GmTGA17 [42] conferred increased ABA sensitivity and drought tolerance in transgenic lines, were confirmed in this study (Figure 3). Moreover, some physiological indices, especially the SWP, were not reported in previous reports [6,27,32,37]. Arabidopsis plants compared with WT plants under normal and drought conditions ( Figure 7E-I).…”
Section: Discussionmentioning
confidence: 53%